Preliminary Study of the Feasibility of a Webcam as a Measuring Tool for Product Geometry (Circular Object Case Study) - Erina Primayanti (IHSA Institute, 2022)
This final straightforward report discusses the initial feasibility study of a webcam as a product geometry measurement tool (a case study of circular objects). Measurements are obtained from reading the 2D imaging surface of the shooting measuring object. In this test the measurement is focused on measuring the diameter of an object in the form of a circle. The image obtained from the results of formal RGB shooting and displayed on a PC monitor by so/Mere webcam, then called using Matlab software. Imaging is processed from RGB format to gray scale and then to monochrome, then the diameter of the image surface is calculated.